Income Inequality in Macedonia: Mechanisms and Solutions - Tevdovski, Dragan (Center for Economic Analysis, 2015)
The rising income inequalities are one of the most important structural reasons of the global economic crisis. We focus on the income inequality in the country with highest Gini coefficient in Europe – Republic of Macedonia. We argue that there are two main drivers of income inequality in the country: installed neo-liberalism and political patronage system. Neo-liberalism is used as a tool to remove the legislative protection of the workers, to maintain the wages on the miserable low level and to block the redistribution of income from the elites towards the others in the society. The completely opposite system of political patronage and populism is used as a tool of governance. It is based on state related benefits targeted to different groups of citizens and designed to be distributed in small portions and in turns in order to gradually increase the serfdom of the majority of the population from the elites. As a result, the country currently has the highest income inequality in Europe, accompanied by increase of poverty. The article concludes with suggestion of five directions for policy reforms.
Keywords: income inequality, neo-liberalism, political patronage, economic policy